Prospects of climate change effects on crop diseases with particular reference to wheat - Prasad, Pramod; Bhardwaj, Subhash Chander; Thakur, Rajni Kant; Adhikari, Sneha; Gangwar, Om Prakash; Lata, Charu; Kumar, Subodh (Journal of Cereal Research, 2021)
Global climate change has considerably threatened wheat production. Rising global temperature is likely to affect wheat productivity directly or indirectly by shifting the dynamics of various abiotic and biotic factors. Shifting diseases and virulence patterns of plant pathogens is assumed to be a significant event for meeting the global food demand in the future, which in turn is expected to make future modifications in disease resistance breeding. Increasing population, industrialization, burning of fossil fuels, and other human activities are going to cause climatic variations. There would be an increased carbon dioxide (CO2)/ greenhouse gas emissions, temperature, erratic rainfall, and other issues which will have a direct impact on crop production as well as disease and pest situations. In general, the incidence of damping-off, powdery mildew, stem rust, leaf rust, Karnal bunt, Fusarium head blight, and blast on wheat will more likely increase. Stripe rust incidence may decrease on wheat. However, isolates of Puccinia striiformis tritici that are adapted to relatively higher temperatures have been observed since 2000 in many countries. From plant disease management perspective, a precise understanding of a particular disease at field level is required, so that the probable effects of different abiotic and biotic factors under climate change situations could be assessed and estimated comprehensibly. Experts working in different areas of agriculture would have to work through a system approach and prioritize the effects of climate change in a broader context, comprising the entire agro-ecosystem. The current article presents the current status of climate changes in relation to the changing wheat disease spectrum and their management strategies.